THE RELATIONSHIP BETWEEN CORPORATE FINANCIAL PERFORMANCE AND CORPORATE GOVERNANCE: EVIDENCE FROM JORDAN - Zyadat, Dr. Ayed Al- (International Journal of Advanced Science and Technology, 2020)
This study investigates the relationship between corporate financial performance and corporate governance for the industrial corporations listed in Amman stock exchange for the period 2016 – 2017. Corporate financial performance is measured by return on assets and return on equity. The corporate governance includes the board size, board independence, board meetings frequencies, and chief of executive officer duality. The multiple regression analysis is used to test hypotheses. The results show that independent variables namely board size, board independence, and board meetings frequencies significantly affect both of return on assets and return on equities except chief of executive officer duality.